2014
DOI: 10.1016/j.str.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural Interactions between Inhibitor and Substrate Docking Sites Give Insight into Mechanisms of Human PS1 Complexes

Abstract: SummaryPresenilin-mediated endoproteolysis of transmembrane proteins plays a key role in physiological signaling and in the pathogenesis of Alzheimer disease and some cancers. Numerous inhibitors have been found via library screens, but their structural mechanisms remain unknown. We used several biophysical techniques to investigate the structure of human presenilin complexes and the effects of peptidomimetic γ-secretase inhibitors. The complexes are bilobed. The head contains nicastrin ectodomain. The membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
85
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 49 publications
(61 reference statements)
10
85
2
1
Order By: Relevance
“…This model predicts that, in the activated conformation of nicastrin, the lid opens and is relocated away from the putative substrate-binding site, thus allowing substrate recruitment. Supporting this conjecture, nicastrin in γ-secretase was reported to undergo a marked conformational switch in response to inhibitor/substrate binding (24), resulting in the closure of the upper subdomain (likely the large lobe) onto the lower subdomain (the small lobe) and compaction of the overall conformation.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This model predicts that, in the activated conformation of nicastrin, the lid opens and is relocated away from the putative substrate-binding site, thus allowing substrate recruitment. Supporting this conjecture, nicastrin in γ-secretase was reported to undergo a marked conformational switch in response to inhibitor/substrate binding (24), resulting in the closure of the upper subdomain (likely the large lobe) onto the lower subdomain (the small lobe) and compaction of the overall conformation.…”
Section: Resultsmentioning
confidence: 94%
“…γ-Secretase is thought to consist of two subcomplexes (24,29), one containing Pen-2 and PS1-NTF (the N-terminal six TMs), bearing eight TMs, and the other comprising PS1-CTF (the C-terminal three TMs), Aph-1, and nicastrin, possessing 11 TMs. The putative assignment of the lone TM from nicastrin suggests that the subcomplexes Pen-2/PS1-NTF and PS1-CTF/Aph-1/ nicastrin may occupy the thin and thick ends, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests a γ-secretase component other than the catalytic presenilin is responsible for this selective cleavage function. Several EM structures of γ-secretase dating back as far as a decade have demonstrated that the ectodomain of nicastrin sits on top of the extracellular side of the γ-secretase TMDs (24,(49)(50)(51). It would therefore stand to reason that nicastrin itself might act to sterically block substrates with large ectodomains from entering the γ-secretase complex for catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…It seemed possible that the interaction of the substrate with the enzyme might change its oligomeric state and/or its interactions with lipids in a way that facilitated solubilization from membranes. In recent studies of other types of IPs, small substrate mimics or inhibitors induced conformational changes ranging from modest shifts of TMSs and loops seen in rhomboid GlpG crystal structures (69 -71) to widespread domain movements observed in presenilin-containing ␥-secretase complexes using cyroelectron microscopy methods (72). Our results show that the SpoIVFB-TEV-FLAG 2 E44Q⅐Pro-K (1-126)-His 6 complex is efficiently solubilized from membranes with nonionic detergents, as well as with lipid-like zwitterionic detergents ( Fig.…”
Section: Solubilization Of An Immp⅐substratementioning
confidence: 99%